Endoscopic retrograde submucosal tunnel resection for cervical esophageal submucosal tumors via percutaneous gastrostomy: a conceptual approach - Song, Conghua; Li, Xiaomei (Frontiers in Medicine, 2025)
Management of submucosal tumors (SMTs) or subepithelial lesions (SELs) at the cervical esophagus remains technically challenging due to limited maneuvering space and short oral mucosal length for conventional submucosal tunnel endoscopic resection (STER). We propose a novel conceptual approach—endoscopic retrograde submucosal tunnel resection (ER-STER)—which enables retrograde access to cervical esophageal SMTs through a percutaneous endoscopic gastrostomy (PG) and anal submucosal tunnel. This technique could potentially enlarge the working space and reduce manipulation near the upper esophageal sphincter (UES), while introducing uncertainties such as PEG-related morbidity, retrograde tunnel perforation, and mediastinal contamination risk. This hypothesis-generating article outlines the rationale, procedural concept, risk analysis, and a translational roadmap for ER-STER. By shifting tunnel entry to the anal side, ER-STER may address the anatomical limitations of conventional STER and reduce patient discomfort associated with proximal mucosal injury. While still theoretical, this method warrants further exploration for feasibility, safety, and clinical utility.